1985
DOI: 10.1172/jci112174
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic fate of extracted glucose in normal human myocardium.

Abstract: Glucose is an important substrate for myocardial metabolism. This study was designed to determine the effect of circulating metabolic substrates on myocardial glucose extraction and to determine the metabolic fate of glucose in normal human myocardium. Coronary sinus and arterial catheters were placed in 23 healthy male volunteers. 16-"'CjGlucose was infused as a tracer in 10 subjects. 16-'CiGlucose and IU-_3Cilactate were simultaneously infused in the other 13 subjects. Simultaneous blood samples were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
1
7

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(110 citation statements)
references
References 69 publications
(60 reference statements)
6
96
1
7
Order By: Relevance
“…3B). These results are consistent with results of earlier studies in humans using arteriovenous measurements of 1-14 C-lactate and L-U-13 C-lactate (19,25). Greater myocardial extraction of tracer than unlabeled lactate was observed in these studies because of the simultaneous release of unlabeled lactate produced from glycolysis of unlabeled glucose.…”
Section: Figuresupporting
confidence: 92%
See 1 more Smart Citation
“…3B). These results are consistent with results of earlier studies in humans using arteriovenous measurements of 1-14 C-lactate and L-U-13 C-lactate (19,25). Greater myocardial extraction of tracer than unlabeled lactate was observed in these studies because of the simultaneous release of unlabeled lactate produced from glycolysis of unlabeled glucose.…”
Section: Figuresupporting
confidence: 92%
“…To identify the 11 C-metabolites present in ART and CS blood samples, 50 mmol/kg of L-3-13 C-bolus (sodium salt; Cambridge Isotope Laboratories, Inc.) were injected into 8 dogs (2 IL, 1 CLAMP, 2 LACTATE, and 3 LAC/PHEN) immediately after the 11 C-lactate bolus injection. Simultaneous ART and CS blood samples were obtained at 5,10,15,20,25,30,45, and 60 min after 11 C-and 13 C-lactate administration for the measurement of 11 C-lactate, 11 CO 2 (an indicator of lactate oxidation), 11 C-neutral, and 11 C-basic metabolites (17), as well as for measurements of ART 13 C-labeled lactate, pyruvate, glucose, and alanine. Paired ART/CS blood samples were also collected to determine blood gases, plasma substrates (glucose, free fatty acids [FFA], lactate), and insulin at baseline, before 11 C, and 30 and 60 min of imaging.…”
Section: Imaging and Art/cs Sampling Protocolmentioning
confidence: 99%
“…Also, it is calculated under the assumption that all substrates taken up by the myocardium undergo complete oxidation in the steady state. Recent isotope-labeled substrate studies have shown that this is not exactly true (41,53,54). OER overestimates the glucose utilization because -13% is released as lactate (41), whereas lactate and fatty acid utilizations are underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…In isolated working rat heart perfused with glucose as sole substrate, a small part of extracellular glucose taken up by the cell is incorporated into glycogen before entering the glycolytic pathway, 31 whereas this incorporation rate is significantly greater in vivo, when hormones and competing substrates are present. 32 At the other end of the spectrum, glycogen is rapidly broken down when glycogen phosphorylase is stimulated by epinephrine or glucagon. 31 Glycogen phosphorylase is the main regulator of glycogenolysis and one of the best-studied enzymes.…”
Section: Glycogen Metabolismmentioning
confidence: 99%